FAKTOR - FAKTOR YANG MEMPENGARUHI PEMANFAATAN TEKNOLOGI INFORMASI PADA KANTOR AKUNTAN PUBLIK (KAP) JAWA TENGAH - Badrul Huda, 12.05.52.0146; Himawan, Arief (Students Journal of Accounting and Banking, 2016)
This research is motivated by the development of information technology, especially for auditors dealing with clients from the outside and limited time. The purpose of this study was to describe the influence of social factors, conformity duty, long-term consequences, affect, complexity and conditions memfasilitaasi the utilization of information technology in Central Java.Â  The population of this study is the KAP located in Central Java are registered with the Insitute Akuntan Publik Indonesia (IAPI) in January 2016. The sampling method used Concinience Sampling method. The sample in this study is 23 KAP by the number of 59 respondents. Data were collected by questionnaire directly performed at KAP is located in central java to Surakarta, Semarang and Purwokerto. Data analysis using linear regression models. The results of this study the suitability of variable assignment addressing significant positive effect. social variables, complexity menunujukan positive effect was not significant and variable Affect showed a significant negative influence as well as the long-term consequences, conditions that facilitate showed significant negative effect on the utilization of information technology. Â Keywords: Social, Suitability Task, Long-term Consequences, Affect, Complexity, Conditions That Facilitate, Utilization of Information Technology, Information Technology, Auditor